Firn cold content evolution at nine sites on the Greenland ice sheet between 1998 and 2017. Issue 258 (29th August 2020) - Vandecrux, B.; Fausto, R. S.; van As, D.; Colgan, W.; Langen, P. L.; Haubner, K.; Ingeman-Nielsen, T.; Heilig, A.; Stevens, C. M.; MacFerrin, M.; Niwano, M.; Steffen, K.; et al.
Abstract: Current sea-level rise partly stems from increased surface melting and meltwater runoff from the Greenland ice sheet. Multi-year snow, also known as firn, covers about 80% of the ice sheet and retains part of the surface meltwater. Since the firn cold content integrates its physical and thermal characteristics, it is a valuable tool for determining the meltwater-retention potential of firn. We use gap-filled climatological data from nine automatic weather stations in the ice-sheet accumulation area to drive a surface-energy-budget and firn model, validated against firn density and temperature observations, over the 1998–2017 period. Our results show a stable top 20 m firn cold content (CC20 ) at most sites. Only at the lower-elevation Dye-2 site did CC20 decrease, by 24% in 2012, before recovering to its original value by 2017. Heat conduction towards the surface is the main process feeding CC20 at all nine sites, while CC20 reduction occurs through low-cold-content fresh-snow addition at the surface during snowfall and latent-heat release when meltwater refreezes. Our simulations suggest that firn densification, while reducing pore space for meltwater retention, increases the firn cold content, enhances near-surface meltwater refreezing and potentially sets favourable conditions for ice-slab formation.